THE INFLUENCE OF LEADERSHIP STYLE AND EMPLOYEES MOTIVATION ON SHIP CERTIFICATION SERVICES AT THE DIRECTORATE OF SHIPPING AND MARINE DIRECTORATE GENERAL OF MARINE TRANSPORTATION, MINISTRY OF TRANSPORTATION - Zaman Zaini; Astri Wahyuningsih (IJESS International Journal of Education and Social Science, 2022)
The purpose of this research is to analyze the magnitude of the influence of the style of leadership and motivation against the ship Certification on Shipping Directorate and Directorate General of Sea Transportation Kepelautan the Ministry of transportation. The theory used in this study refers to the opinion of Tamami (2015), that there are influences between leadership style and motivation towards the Ministry. The research method used is the quantitative methods through the dissemination of a questionnaire, with a total population of 119 people and the sample were 54 people respondents, based on the Slovin formula. Based on the results of the research with the use of linear regression analysis for partial double and with the help of SPSS 23 shows that: partially showed that leadership style has a positive and significant influence of 44.2% against Ministry.In the second partial results showed that motivation has a significant and positive influence of 14.9% against.Free variable style of leadership and motivation are jointly tested with test F prove positive and significant influence towards services and the magnitude of the influence Coefficient Determination value as seen from (R2) was 49.1%.